Biphasic Squamoid Alveolar Papillary Renal Cell Carcinoma: Case Report and Review of the Literature. Issue 6 (November 2017) - Hes, Ondrej; Alaghehbandan, Reza; Rogala, Joanna; Michal, Michal
Abstract : Abstract: We describe a case of 45-year-old white woman with multiple cortical adenomas and papillary renal cell carcinomas (PRCC) in the left kidney, followed by occurrence of multiple cortical adenoma, PRCCs, and 2 so-called biphasic squamoid alveolar PRCCs in the right kidney. Biphasic squamoid alveolar PRCC has recently been introduced as a new entity. These tumors are characterized by a dual-cell population composed of large eosinophilic squamoid cells and smaller basophilic cells identical to those of type 1 PRCC. Immunohistochemically, all tumors are positive for cytokeratin 7, epithelial membrane antigene, vimentin, and cyclin D1. So far multiple numerical chromosomal changes have been disclosed by molecular analysis so far, the most frequent being gains of chromosomes 7 and 17. This review discusses the basic clinical and pathological features of biphasic squamoid alveolar PRCC including historic perspective, biologic behavior, gross and histologic features including immunohistochemistry and molecular genetics, as well as the and differential diagnosis.